Tratamento diferenciado: sobre reconhecimento e consideração em torno do sistema biomédico no Alto Trombetas - FIDELIS, Juliana Cardoso (Universidade Federal do Pará, 2021)
This research presents aspects of claims and strategies of access to biomedical health services, originally reserved for the Mineração Rio do Norte employees, as they have been presented by eight comunidades remanescentes de quilombo in Trombetas (Oriximiná / PA). It is the demand for recognition and consideration as moral and rights subjects forged by the quilombolas living in the Território Alto Trombetas II, who, organized, negotiate access with Mineração Rio do Norte to conventional/ hegemonic medicine. In this context, considering the insufficiency of public services rendered in several segments in the territory, as well as the transformations of the "traditional health model" operating based on knowledge passed down through generations and still activated in the comunidades, it is intended to present reflections on the conditions of access to biomedical services, how they are experienced by the populations and dealt with in the discussions/speeches related to the mining company. In this way, we start from the hypothesis that the liberation and the conditions of access to these services constitutes a moral issue of consideration, based on the development of a notion of "differentiated health", that considers them and that enables them to perceive social esteem, as moral and rights subjects. This research develops through ethnographic work that is methodologically based on the multisituated approach, by which we follow the fundamental relationships based on the emerging discourses that make up the fields of negotiation and understandings about recognition.